Contest in Nanai Shamanic Tales - Tatiana Bulgakova (Journal of Ethnology and Folkloristics)
The tale motif of the shamanic tale competition is examined with due regard for the interpretation given by the Nanai storyteller-shamans from the standpoint of their personal spiritual experience. In shamanic practice it is not the personal ability (skill or physical power) that provides a challenger victory in conflict, but obtaining spirits-helpers more powerful than those of his or her rival. The predominate role of these fantastic personages/helpers in tales that represent invisible spirit helpers perform real shamanic praxis, explains the loser’s unconditional submission and readiness to sacrifice their freedom or life to the winner. It also clarifies the motivation of the initiators of these contests and games: by means of gathering a great number of competitors, such shamans solve their personal spiritual problems, such as the need to overcome their adversaries or find allies in the struggle against their opponents.